PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIIB SMPN 8 TANAH PUTIH TAHUN PELAJARAN 2015/2016. - ', Hermiyati; ', Darmawati; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study is classroom action research (PTK) which aims to improve learning outcomes ipa students with cooperative learning model students teams achievement division (STAD) on grade VIIB SMPN 8 Tanah Putih in the academic year 2015/2016. The study was conducted in March-April 2016. The subjects were VIIB grade students of SMPN 8 Tanah Putih 2015/2016 school year with the number of 26 people (12 students and 14 female students). The study took place during the second cycle in which the first cycle with the matter determines ecosystems and interconnected between the components of the ecosystem and the second cycle with the material identifies the importance of the diversity of life in the preservation of ecosystems conducted 6 meetings including daily tests. Parameters measured were the activities and student learning outcomes which consists of the absorption of students and student learning completeness, awards groups, student activities and teacher's activities. When implementing the learning activities consisting of four indicators and activity when carrying out the percentage of groups that are observed by teachers and teacher activity by giving the check mark (?) during activities diobservasikan by the observer. Absorptive capacity of the students in the first cycle of 76.53% (enough) and the second cycle of 82.5% (good). Mastery learning in the first cycle were completed and 73.07% increased in the second cycle is 88.46%. Group awards in the first cycle there is one super group and the second cycle there are 3 super groups. The average activity of students in the first cycle of 82.20% (excellent) and the second cycle increased to 84.13% (excellent). The average teacher activity increased by 85% (excellent) and the second cycle 95% (excellent). From these results it can be concluded that the model type STAD cooperative learning can enhance the biological activity and learning outcomes VIIB grade students of SMPN 8 Tanah Putih in academic year 2015/2016.Keywords: Learning Outcomes, Model Cooperative, Kooperati Type STAD